Review of Odontoscelio Kieffer, 1905 (Platygastroidea, Scelionidae) with the description of two new species from India - Veenakumari, Kamalanathan; Mohanraj, Prashanth (European Journal of Taxonomy, 2021)
All species of Odontoscelio Kieffer, 1905 are imaged, with keys provided to all known males and females in this genus. Two new species, O. agnieleae sp. nov. and O. spinosus sp. nov., are described from India. The generic concept of the genus Odontoscelio is discussed. The presence of axillular spines differentiates this genus from other teleasines such as Dvivarnus Rajmohana & Veenakumari, 2011, Gryonoides Dodd, 1920 and the Trimorus carus (Nixon, 1936) species group, which possess lateral mesoscutellar spines.